Effect of Oat Lotion Toward Itching Sensation in Hemodialysis Patients with Pruritus at Hospitals - Toruan, Elisabeth Novita Angriani L.; Tanjung, Dudut; Siregar, Cholina Trisa (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
The itching sensation felt by hemodialysis patients who experience pruritus causes discomfort and can even affect the patient's quality of life. Complementary therapy in the form of topical such as oat lotion can be done to overcome the itching sensation in hemodialysis patients who experience pruritus. The purpose of this research is to identify the effect of oat lotion toward itching sensation on hemodialysis patients who experienced pruritus at Medan City Hospital. Data is collected using a questionnaire consisting of a demographic data questionnaire, 5D-IS, and self-reported form. This research uses a quasi-experimental study with a total of 80 respondents consisting of 40 respondents from the intervention group and 40 respondents from the control group selected by simple random sampling technique. The results of statistical analysis with the Mann Whitney U Test showed that there is a difference in itching sensation between the intervention group and the control group after administration of oat lotion (p < 0.05).